Cashless payment and economic growth - Hock-Han Tee; Hway-Boon Ong (Financial Innovation, 2016)
Background: This study examines the effect of adopting cashless payment in five European Union (EU) countries, namely, Austria, Belgium, France, Germany, and Portugal, for the period of 2000-2012. Methods: The within and between effect of adopting cheque payment, telegraphic transfer, card payment and electronic money on these EU's economy are examined by applying the Pedroni residual cointergration and Panel Vector Error Correction Model (VECM). Results: There is short run causality running from cheque payment to telegraphic transfer and card payment, as well as causality running telegraphic transfer to card payment. In the long run, there is significant effect of adopting cashless payment on the economy of the five EU countries. Conclusions: The adoption of one type of cashless payment will affect another type of cashless payment in the short run. The impact of adopting cashless payment on economic growth can only be significantly observed in the long run. Hence, any policy that promotes cashless payment will not affect the economy immediately.
Keywords: 650